COVID-19 in pediatrics: Genetic susceptibility - Glessner, Joseph T.; Chang, Xiao; Mentch, Frank; Qu, Huiqi; Abrams, Debra J.; Thomas, Alexandria; Sleiman, Patrick M. A.; Hakonarson, Hakon (Frontiers in Genetics, 2022)
The uptick in the infection with SARS-CoV-2 has resulted in a worldwide COVID-19 pandemic, which has created troublesome health and economic problems. We performed case-control meta-analyses in both African and European ethnicity COVID-19 disease cases based on lab test and phenotypic criteria. All cases had laboratory-confirmed SARS-CoV-2 infection. We uniquely investigate COVID infection genetics in a pediatric population. Our cohort has a large African ancestry component, also unique to our study. We tested for genetic variant association in 498 cases vs. 1533 controls of African ancestry and 271 cases vs. 855 controls of European ancestry. We acknowledge that the sample size is relatively small, owing to the smaller prevalence of COVID infection among pediatric individuals. The average age of COVID-19 cases was 13 years. Increasing the pediatric global representation in genetic studies enhances the ability to detect novel associations. Our findings support the notion that some genetic variants, most notably at the SEMA6D, FMN1, ACTN1, PDS5B, NFIA, ADGRL3, MMP27, TENM3, SPRY4, MNS1, and RSU1 loci, in addition to CCR9, CXCR6, FYCO1, LZTFL1, TDGF1, CCR1, CCR2, CCR3, CCR5, MAPT-AS1, LCP1, and IFNAR2, these gene variants can indeed affect susceptibility to infection rather than progression to severe COVID-19 once infected. Reviewing the biological roles of genes implicated here, NFIA looks to be most interesting as it recognizes and binds a palindromic sequence present in viral and cellular promoters and in the origin of replication of adenovirus type 2.